PENGEMBANGAN CUSTOMER RELATIONSHIP MANAGEMENT - Frans Richard Kodong (Telematika, 2011)
CRM (Customer Relationship Management) is a computer-based management system or an integrated information system that handles the relationship between the company and its customers with the aim of increasing corporate value in the eyes of its customers. Various research has been done, shows that retaining existing customers is more profitable than attracting new customers. CRM covers all aspects relating to prospects and customers today. CRM is part of an Enterprise Information System. This paper will explain the concept of Information System at the Company, CRM and e-CRM technology based on web. One application of the above technology is the application of CRM in enterprise applications for the property.